Paediatric respiratory infections: impact on cardiopulmonary indicators - Bellsham-Revell, Hannah (Henry Stewart Talks, 2025)
Paediatric Respiratory Infections, Vital signs and symptoms of paediatric respiratory infections, Managing paediatric respiratory infections